A programming approach to the numerical analysis of elasto-plastic continua - Dittmer, Colin Thomas (Department of Civil Engineering, 2023)
The application of a kinematic minimum principle involving a continuous functional subject to inequality constraints is described for the incremental analysis of elasto-plastic continua. A simple algorithm is used for solution of the resulting mathematical programming problem. The formulation is presented for problems in plane stress, plane strain or axial symmetry, using triangular constant strain finite elements, and is extended to the use of cubic quadrilateral isoparametric elements for which a numerical integration technique is employed to account for elasto-plastic interfaces within elements. The material is assumed to obey the von Mises yield condition, and be either elastic-perfectly plastic or linear kinematic hardening. Computational details and solution techniques are described, and numerical examples compared with experimental and numerical results in the literature. Some assessment is made of the relative computational efficiency of the method.